DETERMINANTS OF ISLAMIC BANK PROFITABILITY: THE CASE OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - Aisyah, Esy Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Profitability is an assessment of a company's financial performance that reflects the efficiency and effectiveness of the company's performance. This study aims to analyze the role of NPF in mediating the effect of FDR and BOPO on the profitability (ROA) of Islamic banks. This study uses 11 IslamicCommercial Banks in Indonesia by purposive sampling technique. The test was carried out by the PLS (Partial Least Square) method with the SmartPLS program. Based on the evaluation results, the structural model, this research model has a value of 0.752, which means that this model has a relevant predictive value. The results of PLS analysis prove that FDR does not affect ROA, BOPO and NPF have a negative effect on ROA, FDR has a negative effect on NPF, and BOPO has a positive impact on NPF. And based on the results of the analysis of the mediation effect test, it proves that NPF partially mediates the relationship between FDR and BOPO on ROA. The implementation of this research is that to increase the profitability of Islamic banks; companies should be able to channel financing effectively and maintain efficiency by controlling operational costs to reduce the NPF level of Islamic banks.